An Unusual Case of Streptococcus pyogenes Causing Ruptured Aortic Mycotic Aneurysm - Ali Someili; Anjali Shroff (Case Reports in Infectious Diseases)
A 70-year-old male with a complex past medical history presents with confusion and slurred speech for 24 hours. His exam was unremarkable, and his CT head was negative. Both his C-reactive protein and white blood cell count were elevated. As part of the delirium workup, blood cultures were done which grew Streptococcus pyogenes with no obvious source. He was treated with appropriate antibiotics. To determine the source, a white blood cell scan was done, which showed increased localization within a left-sided upper mediastinum mass. Subsequently, chest CT scan with contrast showed an acute type B aortic dissection with mycotic aneurysm. Consequently, he was taken urgently for surgical management. He completed 6 weeks of penicillin G and was discharged to a rehabilitation center. This case illustrates both a rare entity, mycotic aneurysm secondary to Streptococcus pyogenes, and the importance of getting an Infectious Diseases consult in the setting of an unknown source of bacteremia.